Suppression of TGF-β1 signaling by Matrigel via FAK signaling in cultured human trabecular meshwork cells - Yuan Zhang (Nature Portfolio, 2021)
Abstract The trabecular meshwork (TM) is composed of TM cells and beams of the extracellular matrix, together contributing to aqueous humor (AH) outflow resistance. Herein, we validated that our culture system on 2D Matrigel expressed putative TM markers and myocilin, of which the latter was upregulated by dexamethasone. Continuous passage of these cells on 2D Matrigel resulted in a gradual loss of expression of these markers. However, such a loss was restored by seeding cells in 3D Matrigel where expression of TM markers was further upregulated upon continuous passage. In contrast, TM cells seeded on fibronectin, collagen I/IV, or laminin lost expression of these markers and turned into myofibroblasts with expression of αSMA, which were dose-dependently upregulated by TGF-β1/TGF-β2. TM cells in 3D Matrigel also expressed TGF-β1/TGF-β3 despite challenge of TGF-β1. The maintenance of TM phenotype by 3D Matrigel was linked to inhibition of canonical TGF-β signaling and activation of pFAK-pSrc-pP190RhoGAP-P120RasGAP signaling. These findings indicate that basement membrane matrix with low rigidity plays an active role in maintaining TM phenotype in the presence of TGF-β1 and shed light on its physiological role. Furthermore, abnormal matrices may perpetuate the pathological TM phenotype when the level of TGF-β2 is elevated in glaucoma patients.